Comparative of the Quality of Cooking Oil With Four Times Frying on Packaged and Bulk Cooking Oil - NICO ARDIAWAN PUTRA NICO; Rima Azara (jurnal makanan tropis dan teknologi agroindustri, 2021)
This study aims to determine changes in the quality of packaged cooking oil and bulk cooking oil due to the repeated frying process. This research was conducted using a factorial randomized block design (RAK) with the first factor being the type of cooking oil, namely A1 (packaged oil) and A2 (bulk oil) and frying treatment namely P1 (first frying), P2 (second frying pan), P3 (third frying pan). , and P4 (fourth frying pan). The variables measured were free fatty acids, peroxide number, water content, color, and organoleptic aroma and color. The research data were analyzed using Analysis of Variance (ANOVA), if the results of the analysis showed a significant difference, then the Honest Significant Difference (BNJ) test was continued with a level of 5%. The results showed that the treatment using packaged cooking oil and bulk cooking oil with repeated frying treatment had a significant effect on the parameters of free fatty acids, peroxide value, physical color test and organoleptic tests (aroma and color), and had no significant effect on the water content value. The best treatment parameters in this study were packaged cooking oil with the first frying treatment (A1P1) with a free fatty acid value of 0.06%, a peroxide value of 3.42%, a redness value of 4.77, a yellowness value of 20.00, a level of 0.11% water, and the organoleptic test value for aroma is 4.00 (like-very like) and color 3.90 (like-very much).